Northern Russian peasant house at the turn of the 20th–21st centuries - Usov, Aleksei (project baikal, 2025)
The article is devoted to the study of the Russian North peasant house at the present stage of its existence. The research aim is to find and analyze the transformation of some iconic elements of the architectural structure and layout as well as the actualization of innovations in folk dwelling. The research empirical basis consists of the materials obtained during 11 architectural and ethnographic expeditions to survey cultural landscapes and monuments of traditional culture in rural historical settlements of the Arkhangelsk and Murmansk regions.
Keywords: Russian North; cultural landscape; wooden architecture; traditional culture; dwelling